2023
DOI: 10.3390/nu15030765
|View full text |Cite
|
Sign up to set email alerts
|

Healthful and Unhealthful Plant-Based Diets and Chronic Obstructive Pulmonary Disease in U.S. Adults: Prospective Study

Abstract: Background: Despite the potential protective effect of a plant-based diet against chronic obstructive pulmonary disease (COPD), it remains unknown whether intake of different types of plant foods is beneficial for COPD. Our aims were to determine whether adherence to the healthful version of a plant-based diet (healthful Plant-based Diet Index (hPDI)) is associated with a lower COPD risk, whereas adherence to the unhealthful version (unhealthful Plant-based Diet Index (uPDI)) is associated with a higher COPD r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Pervasive experimental evidence has demonstrated that, in general, a plant-based diet is beneficial to health, largely because of its alignment with global dietary recommendations for chronic disease prevention and management [ 17 , 22 , [34] , [35] , [36] , [37] , [38] , [39] ]. Such a regimen can enhance metabolic regulation, inflammation resistance, and oxidation processes through the consumption of a nourishing plant-based diet replete with fiber-rich and high-quality protein-filled food sources, thereby contributing to the reduction of chronic illnesses [ [40] , [41] , [42] , [43] , [44] , [45] ].…”
Section: Discussionmentioning
confidence: 99%
“…Pervasive experimental evidence has demonstrated that, in general, a plant-based diet is beneficial to health, largely because of its alignment with global dietary recommendations for chronic disease prevention and management [ 17 , 22 , [34] , [35] , [36] , [37] , [38] , [39] ]. Such a regimen can enhance metabolic regulation, inflammation resistance, and oxidation processes through the consumption of a nourishing plant-based diet replete with fiber-rich and high-quality protein-filled food sources, thereby contributing to the reduction of chronic illnesses [ [40] , [41] , [42] , [43] , [44] , [45] ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that high protein concentration in the everyday nutrition reduces COPD exacerbations [13]. Moreover; the nutritional status of lung cancer patients has been closely associated with treatment efficiency and survival [14][15][16][17][18]. In our current study we evaluated the chronic obstructive disease of the patients along with their cancer treatment and their nutritional status and metabolic rate, in an effort to identify how these three parameters interact.…”
Section: Ivyspringmentioning
confidence: 99%